2011
DOI: 10.1080/03650340.2010.540011
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation of soil nutrients under the influence of different organic amendments

Abstract: Maintenance of tropical soil quality for crop production without damaging the environment is a challenge and thus the development of an efficient nutrientmanagement technique is important. Soil amendment by organic manures has been widely accepted as an efficient nutrient-management technique in tropical agriculture. In this study, a long-term laboratory experiment was conducted to investigate the influence of organic manures of different sources (e.g. cattle manure, poultry manure, vermicompost and oil cakes)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
6
5
0
Order By: Relevance
“…This means that soil pH decreased as the N rate of M and F addition increased. Our findings are consistent with previous reports of decreased soil pH with increasing rates of ammoniacal N fertilizer used (Mikha et al, 2006; Fageria et al, 2010; Das et al, 2012).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This means that soil pH decreased as the N rate of M and F addition increased. Our findings are consistent with previous reports of decreased soil pH with increasing rates of ammoniacal N fertilizer used (Mikha et al, 2006; Fageria et al, 2010; Das et al, 2012).…”
Section: Resultssupporting
confidence: 93%
“…1B). This data agrees with previous reports that an increase in soil EC occurred as the rates of ammoniacal fertilizer and manure increased (Chang et al, 1991; Turner et al, 2010; Das et al, 2012). After 5 yr of continuous manure applications, soil EC reached a maximum value of 0.84 dS m –1 for HM treatment in 2011 (Tables 3).…”
Section: Resultssupporting
confidence: 93%
“…The fresh manure rich with labile C and N fractions added every two years could contribute to the soil pH reduction compared with DT-6, where the labile C and N fractions could be less available for microbial activity and their denitrification and respiration processes. Overall, our results are consistent with previously reported research of decreasing soil pH with increasing N rates [ 12 , 32 33 ] regardless to the tillage treatments.…”
Section: Discussionsupporting
confidence: 93%
“…Results from this study showed that the addition of mulch from T. diversifolia or C. cajan did not substantially affect soil chemistry, including soil pH. Similarly, Amusan et al [26] and Das et al [27] did not observe changes in soil pH when either manure or biomass or a combination of manure and biomass were added to an acidic soil in southwestern Nigeria and India. The lack of a significant increase in soil pH may also be due to the smaller amount of mulch biomass added from T. diversifolia or C. cajan compared to other studies [28].…”
Section: Discussionsupporting
confidence: 52%